2017
DOI: 10.1002/cctc.201601503
|View full text |Cite
|
Sign up to set email alerts
|

Design of an Autoreduced Copper in Carbon Nanotube Catalyst to Realize the Precisely Selective Hydrogenation of Dimethyl Oxalate

Abstract: An autoreduced catalyst that comprised Cu nanoparticles encapsulated inside the nanochannels of carbon nanotubes (Cu@CNTs) was designed and prepared. As a result of the interaction of Cu species with the electron‐deficient interior surface of the CNTs, calcination could realize the autoreduction of copper oxide directly with CNTs as the reductant. In the hydrogenation of dimethyl oxalate (DMO), the autoreduced Cu@CNTs catalyst, which did not need to be prereduced, exhibited an excellent catalytic activity, hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 44 publications
1
15
0
Order By: Relevance
“…Ai et al. reported that the auto‐reduction of copper oxides with carbon nanotubes (CNTs) could be directly realized, owing to the interaction of copper species with the electron deficient interior surface of CNTs . After reduction (Figure D), the strong diffraction peak at 2 θ =43.3° along with two small ones at 50.4° and 74.1° were assigned to Cu species (JCPDS 04‐0836), whereas the weak diffraction peak at 36.4° was characteristic of Cu 2 O .…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…Ai et al. reported that the auto‐reduction of copper oxides with carbon nanotubes (CNTs) could be directly realized, owing to the interaction of copper species with the electron deficient interior surface of CNTs . After reduction (Figure D), the strong diffraction peak at 2 θ =43.3° along with two small ones at 50.4° and 74.1° were assigned to Cu species (JCPDS 04‐0836), whereas the weak diffraction peak at 36.4° was characteristic of Cu 2 O .…”
Section: Resultssupporting
confidence: 86%
“…As shown in Figure B, all the samples continuously lost weight from room temperature to 300 °C, which was probably attributed to the evaporation of the absorbed water (<120 °C) and the loss of crystal water, along with well dispersed β‐CD (120–300 °C). With further elevating the temperature, the following weight loss was mainly owing to the transformation of bulk CuO to into Cu 2 O or the collapse of the silica skeleton . The inset picture of Figure B indicated that the Cu‐SiO 2 catalyst exhibited the least weight loss before 300 °C and continued to slight weight loss, whereas the 0.1CD‐Cu‐SiO 2 sample was more stable at high temperature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[33] For Cu/CNT catalysts, diffraction peaks due to Cu 2 Oand Cu metal could easily be distinguished, which indicated that facile reduction of copper speciesb yt he CNT support tookp lace even in the absence of hydrogen. [34,35] In contrast,t he intensity of the Cu-metal peaks of Cu/CNTs -T decreased sharply,b ecauset hermal treatment removed most of the surface oxygen-containing functional groups of CNTs, which led to decreasedr educibility of the CNTs. [34] For Cu/xB-CNTsc atalysts, due to the strong interaction of boron with oxygen-containing species, the oxygen-containing functional groups were partly retained on the surface of xB-CNTs( Figure 3a nd Table 1).…”
Section: Structure and Surface Properties Of Boron-doped Cnt-supportementioning
confidence: 99%
“…7 However, the low Hüttig temperature (134 C, the temperature at which defective atoms will diffuse) and Tamman temperature (405 C, the temperature at which bulk atoms will be mobile) generate the issue of Cu NP agglomeration during the highly exothermic DMO hydrogenation process, hindering the service efficiency of the Cu-based catalysts. 8 The metal support interaction (MSI) has shown great potential in guaranteeing the catalytic activity and stability of the Cu-based catalysts. For this reason, it would be worthwhile elucidating and fully utilizing the support components, affording both adequate active sites and strengthened MSIs.…”
Section: Introductionmentioning
confidence: 99%